Spontaneity and Interactivity Features Displayed in Students’ Transactional Conversations in English for Nursing Program - Wulan, Nawang; I.R. Agustien, Helena; Rukmini, Dwi (English Education Journal, 2018)
This research was intended to analyze how spontaneity and interactivity features were realized in the students’ transactional conversations in English for Nursing Program. This research was a discourse study. The data consisted of five transactional conversations by nursing students in English for Nursing Program. The data were collected through the following steps: recording, transcribing, selecting, counting, and reporting. Then, they were analyzed with spontaneity and interactivity features suggested by Thornburry (2005) and Thornburry and Slade (2006). It was revealed that the most frequent spontaneity features found in the students’ conversations were chunks and filled pauses which indicated that chunks were used to help the students in processing language in real time, and disfluencies were depicted in the form of filled pauses. In addition, the most frequent interactivity features identified were discourse markers which served as the maintenance of the flow of the conversation and predicted what the speakers are going to say next. In conclusion, spontaneity and interactivity features were found in students’ transactional conversations. In addition, it was suggested that the learners need to be exposed to the appropriateness of their use.